A potential serious complication in infants with congenital obstructive uropathy: Secondary pseudohypoaldosteronism - KORKMAZ, LEVENT; HATİPOĞLU, NİHAL; Korkut, Sabriye; Akin, Leyla; Ozdemir, Ahmet; Gunduz, Zubeyde; DURSUN, İSMAİL; Korkmaz, Levent; Kurtoglu, Selim (My University, 2019)
Patients who have secondary pseudohypoaldosteronism (PHA) in addition to hyponatraemia, hyperpotassaemia and high serum aldosterone levels for the age were included in this retrospective study.Among eight patients, seven patients were diagnosed with PHA secondary to obstructive uropathy (OUP), whereas one patient had PHA secondary to ileostomy. Six patients with OUP had simultaneous urinary tract infection (UTI) and in all except one patient, secondary PHA recovered with only UTI treatment before applying surgical correction. All the patients were younger than 3 months age. In three patients with PUV diagnosis, salt wasting recurred in an UTI episode under 3 months of age.